Validated adherence scales used in a measurement-guided medication management approach to target and tailor a medication adherence intervention: a randomised controlled trial. Issue 11 (30th November 2016) - Nguyen, Thi-My-Uyen; La Caze, Adam; Cottrell, Neil
Abstract : Objective: To determine if a targeted and tailored intervention based on a discussion informed by validated adherence scales will improve medication adherence. Design: Prospective randomised trial. Setting: 2 community pharmacies in Brisbane, Australia. Methods: Patients recently initiated on a cardiovascular or oral hypoglycaemic medication within the past 4–12 weeks were recruited from two community pharmacies. Participants identified as non-adherent using the Medication Adherence Questionnaire (MAQ) were randomised into the intervention or control group. The intervention group received a tailored intervention based on a discussion informed by responses to the MAQ, Beliefs about Medicines Questionnaire-Specific and Brief Illness Perception Questionnaire. Adherence was measured using the MAQ at 3 and 6 months following the intervention. Results: A total of 408 patients were assessed for eligibility, from which 152 participants were enrolled into the study. 120 participants were identified as non-adherent using the MAQ and randomised to the 'intervention' or 'control' group. The mean MAQ score at baseline in the intervention and control were similar (1.58: 95% CI (1.38 to 1.78) and 1.60: 95% CI (1.43 to 1.77), respectively). There was a statistically significant improvement in adherence in the intervention group compared to control at 3 months (mean MAQ score 0.42: 95% CI (0.27 to 0.57) vs 1.58: 95% CI (1.42 to 1.75); p<0.001). The significant improvement in MAQ score in the intervention group compared to control was sustained at 6 months (0.48: 95% CI (0.31 to 0.65) vs 1.48: 95% CI (1.27 to 1.69); p<0.001). Conclusions: An intervention that targeted non-adherent participants and tailored to participant-specific reasons for non-adherence was successful at improving medication adherence. Trial registration number: ACTRN12613000162718 ; Results.